Osteoimmune regulation underlies oral implant osseointegration and its perturbation - Albrektsson, T.; Tengvall, P.; Amengual, L.; Coli, P.; Kotsakis, G. A.; Cochran, D. (Frontiers in Immunology, 2023)
Abstract In the field of biomaterials, an endosseous implant is now recognized as an osteoimmuno-modulatory biomaterial and not bioinert. Scientific advances in bone cell biology and in immunology have revealed a close relationship between the bone and immune systems resulting in a field of science called osteoimmunology. These discoveries have allowed for a novel interpretation of osseointegration as representing an osteoimmune reaction rather than a classic bone healing response, in which the activation state of macrophages ((M1–M2 polarization ) appears to play a critical role. Through this viewpoint, the immune system is responsible for isolating the implant biomaterial foreign body by forming bone around the oral implant effectively shielding off the implant from the host bone system, i.e. osseointe-gration becomes a continuous and dynamic host defense reaction. At the same time, this has led to the proposal of a new model of osseointegration, the foreign body equilibrium (FBE). In addition, as an oral wound, the soft tissues are involved with all their innate im-mune characteristics. When implant integration is viewed as an osteoimmune reaction, this has implications for how marginal bone is regulated. For example, while bacteria are consti-tutive components of the soft tissue sulcus, if the inflammatory front and immune reaction is at some distance from the marginal bone, an equilibrium is established. If however, this inflammation approaches the marginal bone, an immune osteoclastic reaction occurs and marginal bone is removed. A number of clinical scenarios can be envisioned whereby the osteoimmune equilibrium is disturbed and marginal bone loss occurs, such as complications of aseptic nature and the synergistic activation of pro-inflammatory pathways (im-plant/wear debris, DAMPs, and PAMPs). Understanding that an implant is a foreign body and that the host reacts osteoimmunologically to shield off the implant allows for a distinc-tion to be drawn between osteoimmunological conditions and peri-implant bone loss. This review will examine dental implant placement as an osteoimmune reaction and its implica-tions for marginal bone loss.